THE EDUCATION OF JAVANESE CHARACTERS IN SERAT WASITAWALA - Maknun, Moch. Lukluil (Analisa: Journal of Social Science and Religion, 2017)
There are abundant Javanese manuscripts in Indonesia. One of the interesting Javanese manuscripts which was reviewed in this paper is Serat Wasitawala. This serat was written in a genre of piwulang. It contains character values that are expected to be the source of the curriculum enrichment for the 2013 national curriculum (Kurtilas) that puts the values of the characters as a priority. Using philology methods and hermeneutical approach, this article reveals content of the text and educational values in Serat Wasitawala, along with the context of writing and its relevance to nowadays education. Serat Wasitawala contains educational values that could represent the concept of Islamic education of Java in the past was written by Mas Demang Warsapradongga. Serat Wasitawala in general was a form of life doctrines both related to God as well as to human beings. The values of character education reflected in it are as follows; wondering, love science, thinking logically, critical, creative, and innovative; religious; honest; responsible; disciplined, hard working, confident boundaries; polite; nationalist; and appreciating diversity. The issues of education that are integral and related with nowadays context include character education/morals, professional teachers, and educational philosophy aimed at seeking perfection of life.